Extracellular CIRP-Impaired Rab26 Restrains EPOR-Mediated Macrophage Polarization in Acute Lung Injury - Zhang, Wen; Wang, Yao; Li, Chuanwei; Xu, Yu; Wang, Xia; Wu, Di; Gao, Zhan; Qian, Hang; You, Zaichun; Zhang, Zhiren; He, Binfeng; Wang, Guansong (Frontiers in Immunology, 2021)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a condition with an imbalanced inflammatory response and delayed resolution of inflammation. Macrophage polarization plays an important role in inflammation and resolution. However, the mechanism of macrophage polarization in ALI/ARDS is not fully understood. We found that mice with lipopolysaccharide administration developed lung injury with the accumulation of extracellular cold-inducible RNA-binding protein (eCIRP) in the lungs. eCIRP, as a damage-associated molecular pattern (DAMP), inhibited M2 macrophage polarization, thereby tipping the balance toward inflammation rather than resolution. Anti-CIRP antibodies reversed such phenotypes. The levels of macrophage erythropoietin (EPO) receptor (EPOR) were reduced after eCIRP treatment. Myeloid-specific EPOR-deficient mice displayed restrained M2 macrophage polarization and impaired inflammation resolution. Mechanistically, eCIRP impaired Rab26, a member of Ras superfamilies of small G proteins, and reduced the transportation of surface EPOR, which resulted in macrophage polarization toward the M1 phenotype. Moreover, EPO treatment hardly promotes M2 polarization in Rab26 knockout (KO) macrophages through EPOR. Collectively, macrophage EPOR signaling is impaired by eCIRP through Rab26 during ALI/ARDS, leading to the restrained M2 macrophage polarization and delayed inflammation resolution. These findings identify a mechanism of persistent inflammation and a potential therapy during ALI/ARDS.